2011
DOI: 10.1016/j.ijsolstr.2011.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Micro-cracks informed damage models for brittle solids

Abstract: a b s t r a c tA class of micro-cracks informed damage models for describing the softening behavior of brittle solids is proposed, in which damage evolution is treated as a consequence of micro-crack propagation. The homogenized stress-strain relation in the cracked microscopic cell defines the degradation tensor, which can be obtained by the equivalence between the averaged strain energy of the microscopic cell and the strain energy density of the homogenized material. This energy equivalence relationship ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…The total displacement field is decomposed based on asymptotic expansion. uε()x=i=0εiui()bold-italicxbold,bold-italicy The decomposition in Equation is substituted into the governing equations, ie, Equations to , and the expansion is performed; the details of the derivation and formal solutions have been reported in the literature (Guedes and Kikuchi; Cheng; Fish et al; Ren et al). Only significant results are detailed, and the resulting macroscopic/microscopic equations will be summarized.…”
Section: Problem Statement and Multiscale Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The total displacement field is decomposed based on asymptotic expansion. uε()x=i=0εiui()bold-italicxbold,bold-italicy The decomposition in Equation is substituted into the governing equations, ie, Equations to , and the expansion is performed; the details of the derivation and formal solutions have been reported in the literature (Guedes and Kikuchi; Cheng; Fish et al; Ren et al). Only significant results are detailed, and the resulting macroscopic/microscopic equations will be summarized.…”
Section: Problem Statement and Multiscale Settingmentioning
confidence: 99%
“…As mentioned above, the HFE of the cracked microcell, Ψ0ε, is defined as Ψ0ε=12σε:eε. In this manuscript, the evolution of damage of the microconstituents is modeled as a consequence of the microcrack propagation; hence, a microcrack informed damage model (MIDM) is employed to model this behavior. Ren et al introduced the relationship between the HFE of the damaged continuum and the averaged HFE of the microcell degraded by microcracks. Volume‐averaging the microcell HFE and the respective microcell displacement field, u ε , over the domain of the microstructure, Ω y , yields the homogenized macroscale HFE trueΨ¯=1Vy()normalΩyΨεdnormalΩ+12normalΓcuε·bold-italich0.25emdnormalΓ where, V y is the microcell volume.…”
Section: Energy Bridging and Damage Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The damage value is allowed to increase only to a value of 1.0. Tensile damage evolution in the AFC bi-scalar damage description is defined by a microcrack-informed damage model (MIDM) proposed by Ren et al (2011). The MIDM was proposed to improve the description of softening behavior of brittle solids by replacing the continuum-scale phenomenological description of tensile damage with a damage evolution function that is derived from a model of fracture in the concrete microstructure.…”
Section: Materials Modelmentioning
confidence: 99%
“…For common reinforced concrete members, lots of experimental investigations have been conducted (Nilson and Arthur 1968;Bathe and Ramaswamg 1979;Priestly and Benzoni 1996;Lehman et al 1995;Phan et al 2007;Hindi 2005;Hindi et al 2005;Wang et al 2014;Afefy and El-Tony 2016;Jiong 2004;Li and Ren 2009;Elmorsi et al 1998;Esmaeily and Shirmohammadi 2014;Shao et al 2005;Zendaoui et al 2016;Ren et al 2010). Previous studies of reinforced concrete members have demonstrated that slender ratio, material property, axial compression ratio, reinforcement ratio, detailing art and stirrups played significant roles in the seismic behavior, especially the hysteretic performance of reinforced concrete members.…”
Section: Introductionmentioning
confidence: 99%